IMPLEMENTASI SISTEM PENERIMAAN SANTRI BARU BERBASIS WEBSITE DI PONDOK PESANTREN AT-TADZKIR MAJA - Sanjaya, Hafidz; Maula Hidayat, Fajar; Purnomo, Dwi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2025)
The At-Tadzkir Maja Islamic Boarding School faces challenges in its new student admission process, which is still conducted manually, making it inefficient and prone to administrative errors. To address this issue, a community service program was carried out by implementing a web-based student admission system. This system is designed to facilitate prospective students in registering online and assist the school administration in managing applicant data more effectively and accurately. The methods used in this program include needs analysis, system design, development, and training for school administrators on how to operate the system. The implementation results indicate that the web-based system enhances the efficiency of the student admission process, reduces paper usage, and provides easier access to information for both prospective students and school staff. With this system, At-Tadzkir Maja Islamic Boarding School is expected to improve its professionalism in managing student admissions and enhance the quality of its educational services.